Instruments for Measuring Patient Safety Competencies in Clinical Settings: A Literature Review - Suciati, Suciati; Asmaningrum, Nurfika; Suhari, Suhari (GLOBAL HEALTH SCIENCE GROUP, 2024)
Patient safety culture has emerged as a global priority necessitating improvement to prevent patient accidents. Measuring the competency of healthcare workers concerning patient safety within health services is essential, and various instruments can be employed for this purpose. This study aims to analyze the instruments used to measure patient safety competency. Method: A systematic review was conducted using the PRISMA protocol and the JBI assessment tool to identify eligible articles. Two electronic databases, PubMed and Google Scholar, were searched. The keywords used in the research included “instrument safety culture in clinical settings”; “Safety culture instrument”;